Molecular markers associated with drug resistance in Plasmodium falciparum parasites in central Africa between 2016 and 2021 - Xu, Wenjie; Zhang, Xuan; Chen, Hualiang; Zhang, Jiaqi; Lu, Qiaoyi; Ruan, Wei; Wang, Xiaoxiao (Frontiers in Public Health, 2023)
Objectives: The widespread occurrence of anti-malarial drug resistance threatens the current efforts to control malaria in African regions. Molecular marker surveillance helps to track the emergence and spread of drug-resistant malaria cases. Methods: A total of 237 Plasmodium falciparum infections imported from central Africa to Zhejiang Province, China, between 2016 and 2021, were investigated. Genomic DNA was extracted from blood samples of each patient and nested PCRs was used to detect molecular markers in k13, Pfcrt and Pfmdr1 genes. The spatial and temporal distributions of the molecular markers were analyzed. Results: A limited polymorphism of k13 was observed, including two nonsynonymous (D464E and K503E) and five synonymous mutations. Wild-type CVMNK of Pfcrt predominated (78.5%), whereas 19.5% of the samples harbored the mutant haplotype, CVIET. The point mutation Y184F and the single mutant haplotype NF of Pfmdr1 were the most frequently observed. The geographical distributions of the Pfcrt and Pfmdr1 haplotypes displayed distinct patterns, with the mutant haplotype of Pfcrt more common in Gabon (53.9%) and Congo (50.0%), and wild haplotypes of Pfmdr1 more frequently found in Cameroon, Angola, and Congo. The prevalence of wild-type CVMNK of Pfcrt increased from 68.5%-74.6% in 2016-2017 to 81.8%-87.5% in 2018-2021. The proportion of wild-type Pfmdr1 also increased from 27.1% in 2016 to 38.5% in 2019. Conclusions: The geographical and temporal distribution of k13, Pfcrt and Pfmdr1 polymorphisms in P. falciparum parasites imported from central Africa between 2016 and 2021 are demonstrated. Our data provides updated evidence that can be used to adjust anti-malarial drug policies in central Africa and China.